Nurse Motivation in Implementing Therapeutic Communication in the Inpatient Room General Perdagangan Hospital - Josep Lubis; Simatupang, Mindo Rahel (PT Inovasi Pratama Internasional, 2023)
Most of human time is for communicating, starting from waking up, working, even to carrying out daily activities, humans cannot be separated from what is called communication. In other words, communication is an inseparable part of human daily life. Communication is a tool for nurses to influence patient behavior and to get success in nursing interventions. This research is descriptive in nature. This study aims to find out how motivated nurses are in implementing therapeutic communication in the General Perdagangan Hospital inpatient room. Sampling in this study using a total sampling of 36 respondents. The results showed that of the 36 respondents in the rose, jasmine and orchid inpatient rooms of the General Perdagangan Hospital it was stated that in therapeutic communication with patients the majority of nurses behaved well by 23 (64%), and the minority behaved badly by 13 (36%). The results of the study showed that of the 36 respondents in the inpatient rooms of roses, jasmine and orchids, the majority of nurses had sufficient ability in therapeutic communication with patients, 24 (67%), and a minority of 4 (11%) had poor ability. It is hoped that health workers will further improve professional therapeutic communication in providing health services to patients.